2009
DOI: 10.7150/ijbs.5.249
|View full text |Cite
|
Sign up to set email alerts
|

In vivo evidence of hepato- and reno-protective effect of garlic oil against sodium nitrite-induced oxidative stress

Abstract: Sodium nitrite (NaNO2), a food color fixative and preservative, contributes to carcinogenesis. We investigated the protective role of garlic oil against NaNO2-induced abnormalities in metabolic biochemical parameters and oxidative status in male albino rats. NaNO2 treatment for a period of three months induced a significant increase in serum levels of glucose, aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), bilirubin, urea and creatinine as well as hepatic AST and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
55
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 37 publications
13
55
0
Order By: Relevance
“…M. emarginata treatment has appreciably normalized the content of protein and urea. In response to STZ treatment, creatinine was increased in the serum, suggesting an impairment of kidney functions [43] . M. emarginata showed a clear improvement in kidney functions, perhaps due to the antioxidant properties.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…M. emarginata treatment has appreciably normalized the content of protein and urea. In response to STZ treatment, creatinine was increased in the serum, suggesting an impairment of kidney functions [43] . M. emarginata showed a clear improvement in kidney functions, perhaps due to the antioxidant properties.…”
Section: Discussionmentioning
confidence: 99%
“…The activities of both glucose-6-phosphatase and fructose-1, 6-bisphosphatase are increased in the liver during the diabetic condition [43] . Treatment with M. emarginata has appreciably normalized the activity of these enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also Monagas,(2010) ,who found that phinolic compound act asantibacterial due to these effects can be their chelating properties on iron, an important oligoelement for heme-utilizing bacteria On the other hand G 7 continued in its increased in bacterial count might be due to nitrate caused dejected host defense immunity ,that led to distribution of bacteria in the tissue ,in addition to immunotoxic effect of nitrate that helped bacterial invasion ,damage tissue and inhibited immune response and led to decreased bacterial clearance in all systemic organ , these result were in agreement with Pannala ,et al, (2003).who found that ingested nitrate is converted by microflora in the gastrointestinal tract to more toxic nitrit .In addintion that nitrate is a source of nitric oxide (NO) and other reactive oxygen as well as nitrogen species such as hydrogen peroxide (H2O2), peroxynitrite (ONOO-) and superoxide anion (O2-), that causes damage cellular membrane through lipid peroxidation (LOP),as a result of high concentration unsaturated fatty acids of phospholipids (Hassan,et al, 2009) . Thus, weakness of the cellular membrane as well as a disturbance of membrane transport that led to damage tissue and impairs liver functions (Ogur ,et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The condition begins from an inequality between the quantity of oxygen needed through the body and the quantity of oxygenated blood that is provided (Maher et al, 2008). Numerous studies have shown that the harmful impact of NaNO 2 induced hypoxia is related to inflammation, oxidative stress and methemoglobinemia, which induce injury and dysfunction of different organs (Al-Gayyar et al, 2014;El-Sheikh and Khalil, 2011;Hassan et al, 2009;Salama et al, 2013).…”
Section: Introductionmentioning
confidence: 99%